(untitled) (International conference on multidisciplinary science, 2026)
This article examines the service sector as an important factor in ensuring employment, sustainable economic growth, and improving living standards in the country. The study’s results show that the service sector’s share of GDP does not meet current global standards, and is significantly lower than in economically developed countries. However, the service sector is currently developing at a relatively rapid pace in Uzbekistan.